2009
DOI: 10.5551/jat.1438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plaque Stabilization by Fluvastatin with Carotid Intima- Medial Elasticity Measured by a Transcutaneous Ultrasonic-Based Tissue Characterization System

Abstract: Aim:As an approach to tissue characterization, we attempted to classify in vivo carotid plaque tissues in terms of arterial wall elasticity instead of echogenicity on B-mode scanning and investigated whether the effect of fluvastatin on carotid elasticity can be detected in hypercholesterolemic patients. Methods: In 170 subjects, simultaneous measurements of intima-media thickness (IMT) and elastic modulus in the circumferential direction (E ) were performed using a new transcutaneous high-resolution Doppler t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Because CIMT has direct implications on morbidity and mortality in humans, 14,25 its measurement in the mouse model for PXE can be an endpoint and can have future implications in determining treatment efficacy in this disease. This study examined the reduction of the CIMT measurements after treatment with magnesium oxide in Abcc6 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because CIMT has direct implications on morbidity and mortality in humans, 14,25 its measurement in the mouse model for PXE can be an endpoint and can have future implications in determining treatment efficacy in this disease. This study examined the reduction of the CIMT measurements after treatment with magnesium oxide in Abcc6 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism by which hs-CRP may contribute to the development of ischemic cardiovascular disease is its role as a marker of inflammatory 30) and atherosclerotic processes 31) , although it is wellknown that hs-CRP is associated with the presence of atherosclerosis [32][33][34][35] . One study concluded that the increased risk of ischemic cardiovascular disease associated with higher CRP may not be causal, but simply a marker, since CRP polymorphisms were not associated with disease risk 13) .…”
Section: Acknowledgementsmentioning
confidence: 99%
“…According to the Cardiovascular Health Study and NOMAS, normal CIMT ranges vary from 0.7 to 0.9 mm in 45- to 75-year-olds [34] and the progression of CIMT – depending on risk factors – can range from 0.01 ± 0.05 mm/year [35]. If low-serum magnesium can potentially cause a significant increase in CIMT in women in this age range (similar to the pathological progression of CIMT), the risk of stroke incidence increases as the CIMT rate of change increases [35], resulting in increased cardiovascular morbidity and mortality [36,37,38]. …”
Section: Magnesium and Cardiovascular Applicationsmentioning
confidence: 99%